Molecular characterization of measles viruses in Turkey (2010–2011): First report of genotype D9 involved in an outbreak in 2011. Issue 12 (19th August 2013) - Kalaycioglu, Atila T.; Baykal, Atakan; Guldemir, Dilek; Bakkaloglu, Zekiye; Korukluoglu, Gulay; Coskun, Aslihan; Torunoglu, Mehmet Ali; Ertek, Mustafa; Durmaz, Riza
Abstract Genetic characterization of measles viruses (MVs) combined with acquisition of epidemiologic information is essential for measles surveillance programs used in determining transmission pathways. This study describes the molecular characterization of 26 MV strains (3 from 2010, 23 from 2011) obtained from urine or throat swabs harvested from patients in Turkey. MV RNA samples (n = 26) were subjected to sequence analysis of 450 nucleotides comprising the most variable C‐terminal region of the nucleoprotein (N) gene. Phylogenetic analysis revealed 20 strains from 2011 belonged to genotype D9, 3 to D4, 2 strains from 2010 to genotype D4 and 1 to genotype B3. This study represents the first report describing the involvement of MV genotype D9 in an outbreak in Turkey. The sequence of the majority of genotype D9 strains was identical to those identified in Russia, Malaysia, Japan, and the UK. Despite lack of sufficient epidemiologic information, the presence of variants observed following phylogenetic analysis suggested that exposure to genotype D9 might have occurred due to importation more than once. Phylogenetic analysis of five genotype D4 strains revealed the presence of four variants. Epidemiological information and phylogenetic analysis suggested that three genotype D4 strains and one genotype B3 strain were associated with importation. This study suggests the presence of pockets of unimmunized individuals making Turkey susceptible to outbreaks. Continuing molecular surveillance of measles strains in Turkey is essential as a means of acquiring epidemiologic information to define viral transmission patterns and determine the effectiveness of measles vaccination programs designed to eliminate this virus. J. Med. Virol. 85:2128–2135, 2013. © 2013 Wiley Periodicals, Inc.